Radiation effect of fractal sierpinski square patch antenna - Khalid Hussein Kuther; Israa Hazem Ali; Riyadh Khlf Ahmed (International Journal of Electrical and Computer Engineering (IJECE), 2020)
Biological tissue interaction with Electromagnetic fields became one of the interesting studies in the last years. Wide variety wireless electronic devices are emerged in day to day life each providing a wireless connection for a certain service such as Global Positioning System, broadcasting systems, mobile communication systems, and networking. In this research article, Fractal Sierpinski Square Patch Antenna is proposed and simulated to operate over L1 frequency range of 1.575 GHz for GPS applications using CST studio Suite where the proposed antenna has been investigated on Carpet shaped substrate made of Arlon 250 AD lossy. The dielectric constant equals to 2.5 and thickness of 1.6 mm. Thickness of patch is 0.6 mm. Also, the electromagnetic fields absorption on the human fingers is investigated where SAR levels are calculated for 0th, 1st, 2nd and 3rd iteration of the Fractal Sierpinski Square Patch Antenna. The results reported that the SAR limit of human finger tissue is enhanced with increasing the number of iteration.